Enhanced thermal conductance of polymer composites through embeddingaligned carbon nanofibers - Dale K. Hensley; Nicholas Roberts; DavidWood (AIMS Materials Science, 2016)
The focus of this work is to find a more efficient method of enhancing the thermal conductance of polymer thin films. This work compares polymer thin films embedded with randomly oriented carbon nanotubes to those with vertically aligned carbon nanofibers. Thin films embedded with carbon nanofibers demonstrated a similar thermal conductance between 40–60 μm and a higher thermal conductance between 25–40 μm than films embedded with carbon nanotubes with similar volume fractions even though carbon nanotubes have a higher thermal conductivity than carbon nanofibers.